If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6.8(x + -3) = -0.2x + 28.6 Reorder the terms: 6.8(-3 + x) = -0.2x + 28.6 (-3 * 6.8 + x * 6.8) = -0.2x + 28.6 (-20.4 + 6.8x) = -0.2x + 28.6 Reorder the terms: -20.4 + 6.8x = 28.6 + -0.2x Solving -20.4 + 6.8x = 28.6 + -0.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.2x' to each side of the equation. -20.4 + 6.8x + 0.2x = 28.6 + -0.2x + 0.2x Combine like terms: 6.8x + 0.2x = 7x -20.4 + 7x = 28.6 + -0.2x + 0.2x Combine like terms: -0.2x + 0.2x = 0.0 -20.4 + 7x = 28.6 + 0.0 -20.4 + 7x = 28.6 Add '20.4' to each side of the equation. -20.4 + 20.4 + 7x = 28.6 + 20.4 Combine like terms: -20.4 + 20.4 = 0.0 0.0 + 7x = 28.6 + 20.4 7x = 28.6 + 20.4 Combine like terms: 28.6 + 20.4 = 49 7x = 49 Divide each side by '7'. x = 7 Simplifying x = 7
| -10x+18=2(9-5x) | | -6(6-7x)=342 | | .2x+2.3=3.5 | | -95-2x=67-8x | | 44-3x=7x-6 | | 80=-16t^2+128t | | 3(2x-3)-4(7-2x)=-30 | | 1-8(x-2)=57 | | (1/3)2= | | 5(3+x)+2x=8+19x | | -z=110 | | 2x+10=3x+50 | | 7m+2=6m+8 | | 12b-9b=12 | | 3x+7=4x+-2 | | 19t=21 | | p=.18x^2+36x+4000 | | 146=6x-2(-7x-3) | | 4(5x-10)+6=5x+10 | | 6y+3=y+13 | | 6.1h=4.3-3.2h | | 6x-3=24x | | -12x=168 | | 14b-9b=10 | | 24x-6=3x | | y=10x-150 | | 24x-3=6x | | -2x+6=6x+2 | | 9(x-10)+6x=-8x+2 | | 5(k+2)+8(k+3)=-1 | | 3x-5=-45-1x | | 12=-2.7t^2+30t+6.5 |